2022
DOI: 10.21595/jfocg.2022.22682
|View full text |Cite
|
Sign up to set email alerts
|

Is jaw functional orthopedics an efficient tool to treat anterior open bite? A retrospective study

Abstract: Anterior Open Bite (AOB) is a malocclusion for which the choice of a treatment protocol it is challenging. There are some protocols that have been shown to be effective for open bite treatment. The aim of this investigation was to study the behavior of overbite during AOB treatment with Jaw Functional Orthopedics (JFO). The behavior of overbite was studied retrospectively in 17 patients treated in the Specialization Course in (JFO – ABO Muriaé (Muriaé, MG Brazil). Monthly overbite measurements in millimeters w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…There are some theories about how JFO modifies the stomatognathic system but none proved. Costa et al [22] found a weak correlation of the mandibular degree of closure (𝑃 = 0,098). No other paper regarding this subject was found in Capes Portal or Medline using key words "anterior open bite", "treatment", "skeletal changes", "mechanism", "dentofacial orthopedics", "jaw functional orthopedics" and "functional orthopedics".…”
Section: Anterior Open Bite Treatment Scientific Evidencementioning
confidence: 97%
“…There are some theories about how JFO modifies the stomatognathic system but none proved. Costa et al [22] found a weak correlation of the mandibular degree of closure (𝑃 = 0,098). No other paper regarding this subject was found in Capes Portal or Medline using key words "anterior open bite", "treatment", "skeletal changes", "mechanism", "dentofacial orthopedics", "jaw functional orthopedics" and "functional orthopedics".…”
Section: Anterior Open Bite Treatment Scientific Evidencementioning
confidence: 97%
“…Soares and Santiago Jr. [16] reported the clinical efficacy of JFO to improve the overbite in AOB treatment with a 𝑃 = 0.003. But there is still no data available about the skeletal behavior due to FOA.…”
Section: Introductionmentioning
confidence: 99%
“…Jaw Functional Orthopedics (JFO) is a growing field with very interesting clinical results in the treatment of malocclusion, dentofacial development problems [1][2][3][4][5][6][7] and Temporomandibular Disorders (TMD) [8,9], but still needs stronger scientific basis [10][11][12].…”
Section: Introductionmentioning
confidence: 99%